Study of psy-markers of mental fatigue - Sikkandhar Musafargani (2018)
Mental fatigue is of central importance in the fields of human factors and ergonomics. A reliable measurement of mental fatigue could allow for improvements in human machine interface designs and increase safety in several domains. At present, numerous studies have used neuroimaging modalities to assess the level of mental fatigue, reporting the rise in cognitive load to be associated with fluctuations of different frequency bands of brain oscillations. However, the results have been inconsistent with some failing to reach the required level of significance. We hypothesised that the lack of consistency could be associated with lack of feasibility to perform the tasks by different individuals. In the present study, we quantified the level of mental fatigue induced due to three different tasks using Magnetoencephalography (MEG) in terms of fluctuations of brain oscillations, namely, Theta (4-8 Hz), Alpha (8-12 Hz) and Beta (12-16 Hz) associated with spatial regions of the brain. Also, the enhancement of mental fatigue was computed in the morning and evening to witness the associated alterations in the specific bands of brain oscillations. The significant results from the experiments aid to interpret the reason for the transition of brain waves and trace the neurophysiology behind the phenomenon. Thus, it provides evident results to utilise these bands of neural oscillation as significant psy-marker of mental fatigue.